S-band multiwavelength ring Brillouin/Raman fiber laser with 20 GHz channel spacing - Ahmad, Harith; Zulkifli, Mohd Zamani; Hassan, Nor Ahya; Harun, Sulaiman Wadi (Optical Society of America, 2012)
We propose and demonstrate a tunable S-band multiwavelength Brillouin/Raman fiber laser (MBRFL) with a tuning range of between 1490 to 1530 nm. The proposed MBRFL is designed around a 7.7 km long dispersion compensating fiber in a simple ring configuration, acting as a nonlinear medium for the generation of multiple wavelengths from stimulated Brillouin scattering (SBS) and also as a nonlinear gain medium for stimulated Raman scattering (SRS) amplification. A laser source with a maximum power of 12 dBm acts as the Brillouin pump (BP), while two 1420 nm laser diodes with a total power of 26 dBm act as the Raman pumps (RPs). The MBRFL can generate a multiwavelength comb consisting of even and odd Stokes at an average power of −12 dBm and −14 dBm respectively, and by separating the even and odd Stokes outputs, a 20 GHz channel spacing is obtained between two consecutive wavelengths. Due to the four-wave mixing (FWM) effect, anti-Stokes lines are also observed. The multiwavelength comb generated is not dependent on the BP, thus providing high stability and repeatability and making it a highly potential source for many real-world applications. This is the first time, to the knowledge of the authors, that a tunable MBRFL has been developed using SRS to obtain gain in the S-band region. © 2012 Optical Society of America